Answer:
Step-by-step explanation:
1.225km is equal to each laps
Step-by-step explanation:
Since Kristy total distance traveled = 29.6km
And Kristy ran 24 laps and later walk 0.2km. it simply implies that
Total distance traveled = distance covered running + distance covered walking
Since we know that
Total distance traveled = 29.6km
distance covered running = 24 laps
distance covered walking = 0.2km
Distance covered running in km = total distance traveled - distance covered walking
Distance covered running in km = 29.6km - 0.2km = 29.4km.
To now find the distance for each lap.
Since we have:
Distance covered running in km = 29.4km.
Distance covered running in lap = 24 laps
i.e
24 laps = 29.4km
1 lap = x
Use cross-multiple
24 laps * x = 29.4km × 1 lap
x = 29.4km / 24
x = 1.225km
Therefore
1.225km is equal to each laps.
Answer:
I think you would do $9.70 times 2. Afterward, you would divide 9.70 by 5 which gives you 1.94. Finally, you add them together, leaving you with. 11.64. I hope I helped with this.
:D
Answer:
1/16
Step-by-step explanation:
<h2><em>
Hope This Helps :)</em></h2><h2><em>
</em></h2>
Answer: I am just hoping that this is the correct answer
Step-by-step explanation:
2(-6 + -5y) + (2y + -8) = 0
(-6 * 2 + -5y * 2) + (2y + -8) = 0
(-12 + -10y) + (2y + -8) = 0
Reorder the terms:
-12 + -10y + (-8 + 2y) = 0
Remove parenthesis around (-8 + 2y)
-12 + -10y + -8 + 2y = 0
Reorder the terms:
-12 + -8 + -10y + 2y = 0
Combine like terms: -12 + -8 = -20
-20 + -10y + 2y = 0
Combine like terms: -10y + 2y = -8y
-20 + -8y = 0
Solving
-20 + -8y = 0
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '20' to each side of the equation.
-20 + 20 + -8y = 0 + 20
Combine like terms: -20 + 20 = 0
0 + -8y = 0 + 20
-8y = 0 + 20
Combine like terms: 0 + 20 = 20
-8y = 20
Divide each side by '-8'.
y = -2.5
Simplifying
y = -2.5
Answer:
The 2 numbers are 14 and 17.
Step-by-step explanation:
Let the 2 numbers be x and y.
x + 11 = 2y
x - 2y = -11...............A
y +20 = 2x
2x - y = 20 ...............B
Multiply equation A by -2:
-2x + 4y = 22............C
Adding B and C :-
3y = 42
y = 14.
Substitute y = 14 in equation A:
x - 2(14) = -11
x = -11 + 28
x = 17.